Comparative Analysis of Promotion Strategies Between MSMEs Fried Shallot Mak Yem and Fried Shallot Rinings in Nganjuk Regency - Pramesti Intan Destari; Siti Ning Farida (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to determine and analyze the comparison of promotional strategies between MSMEs of fried shallots mak yem and fried shallots rinings in Nganjuk Regency. Consumers compare promotional strategies consisting of several dimensions, namely: Advertising, Personal selling, Publicity, Sales Promotion, and Direct Marketing. The method used is quantitative by collecting data through questionnaires using Purposive Sampling techniques in sampling. Respondents in this study were 100 respondents with the following criteria: 1) Consumers of MSME fried shallots mak yem, 2) Consumers of MSME fried shallots rinings, and 3) MSME actors in Nganjuk Regency. The analysis technique used in this study is the Wilcoxon Test, which is a nonparametric statistical method used as an alternative to the Paired T-Test when the data analyzed is not normally distributed. This Wilcoxon test aims to evaluate the differences between two groups of paired data by comparing the value rankings of the observation pairs. The results of this study show that: (1) In the advertising dimension, the average results show that Mak Yem UMKM is superior to Rinings UMKM, (2) In the personal selling dimension, the average results show that Mak Yem UMKM is superior to Rinings UMKM, (3) In the publicity dimension, the average results show that Mak Yem UMKM is superior to Rinings UMKM, (4) In the sales promotion dimension, there is no difference in the average score between Mak Yem and Rinings UMKM, (5) In the direct marketing dimension, the average results show that Mak Yem UMKM is superior to Rinings UMKM.